A contribuição da Enfermagem para aliviar o sofrimento do doente hemato-oncológico: revisão da literatura - Casimiro dos Santos Sá, Eunice Maria (2010)
BACKGROUND: We all agree that suffering is a constant in the life of someone with an oncological disease. According to Wright (2005), suffering is like anguish, pain or physical, emotional and spiritual distress and the reduction or decrease of suffering is the centre, the essence and the heart of the nurse’s clinical practice, and the ethical goal, must be the relief or decrease of the emotional, physical and/or spiritual suffering of the patients and families. Therefore it becomes pertinent to clarify which nursing interventions relieve the suffering of people with hemato-oncologic disease. GOAL: describe and compare studies and identify which nursing interventions contribute to the relief of a hemato-oncologic adult inpatient suffering, emphasising non-physical dimensions od nursing interventions. DESIGN: Systematic Review using the PICOS method. METHOD: Six (6) studies with oncologic participants and different research designs, selected from the search in electronic databases (EBSCO e b-on), were included. RESULTS: The results point to emphasis on the person centred care and not on the disease, in the detachment of the routines and patronizing attitudes, emphasizing the importance of the relational and aide skills, such as listening, respect, individuality, partnership, like adequate and desirable nursing interventions to the patients with any other diseases. CONCLUSION: Nurses interventions were not specific to hemato-oncologic inpatients; the findings point to the simplicity and global use of the nursing interventions, and the importance of these being present in all of nursing practice.